2021
DOI: 10.3390/jcm10091802
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Thrombectomy in Stroke. Experience from Switching from Stent Retriever Only to Stent Retriever Combined with Aspiration Catheter

Abstract: Endovascular treatment is a rapidly evolving technique; therefore, there is a constant need to evaluate this method and its modifications. This paper discusses a single-center experience and the results of switching from the stent retriever only (SO) mechanical thrombectomy (MT) to the combined approach (CA), with a stent retriever and aspiration catheters. Methods: The study involved a retrospective analysis of 70 patients undergoing MT with the use of either SO or CA. The primary endpoint was the frequency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 28 publications
0
9
1
Order By: Relevance
“…Notably, we found first-line SR+CA had more MT passes, longer procedure duration and a similar successful recanalisation rate after first technique alone compared with first-line SR alone with the adjustment for the confounders and PS, which was different from the previous studies reported 7–12 19 20. Three reasons might explain the difference: first, the high incidence of LVO due to LAA was found high in China, which was reported in 52.7% of patients from the ANGEL-ACT registry,21 and patients with LAA were more vascular tortuous.…”
Section: Discussioncontrasting
confidence: 75%
See 3 more Smart Citations
“…Notably, we found first-line SR+CA had more MT passes, longer procedure duration and a similar successful recanalisation rate after first technique alone compared with first-line SR alone with the adjustment for the confounders and PS, which was different from the previous studies reported 7–12 19 20. Three reasons might explain the difference: first, the high incidence of LVO due to LAA was found high in China, which was reported in 52.7% of patients from the ANGEL-ACT registry,21 and patients with LAA were more vascular tortuous.…”
Section: Discussioncontrasting
confidence: 75%
“…In real-world practice, first-line SR+CA might increase additional costs compared with first-line SR alone. Meder et al reported that switching from SR alone to SR+CA could increase approximately 30% of the direct costs of MT in their institution 8. In addition, the AC was not widely used throughout China during the study period, resulting in its non-availability in some hospitals 16.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Blood flow restoration in the occluded vessel can be obtained mechanically through three main methods: using a stent retriever, aspiration catheters and combining both these methods. Many trials comparing those techniques have proven the equality of SO and CM, and many have demonstrated the superiority of CM over AO and SO [ 5 , 6 , 7 , 8 , 9 ]. Of the two recent network meta-analyses, both suggested CM to be superior in terms of technical efficacy with similar safety and clinical outcomes compared to AO and SO [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%